How Does Song of Moses in the Exodus 15:8-14, Teach Education? (LXX-Rahlfs) - Philip Suciadi Chia; Juanda Juanda (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2022)
There are various ways to teach people to be able to hope and rely on God. Behold, LORD, who among the gods is like you? Who is like you, wonderful in holiness? Who can work miracles and mighty acts like yours? This article argues that the song of Moses teaches the faith lesson. The miracle of God brings healing and comfort. Therefore, God’s deliverance should encourage the people of God to trust the Lord more in their difficulties.